Leveraging technology in dispute resolution: analysing its integration and implementation in Kenya - Ali, N. A. (Strathmore University, 2025)
The integration of technology in dispute resolution has been gradually reshaping Kenya's dispute resolution landscape, transforming traditional and online methods alike. Technologies such as artificial intelligence, blockchain, and virtual platforms are increasingly being utilized to enhance efficiency, transparency, and accessibility in resolving disputes. This study aims to explore the current state of technology adoption in Kenya's dispute resolution system, focusing on the opportunities and challenges presented by these innovations. Specifically, the research will examine the concept of technology in dispute resolution, the existing legal and regulatory framework governing the use of technology in Kenya’s dispute resolution system and identify opportunities as well as gaps that may hinder its effective implementation and enforcement. Employing a doctrinal research methodology, the study will analyse primary sources and relevant secondary data to evaluate the technological landscape and regulatory environment surrounding dispute resolution practices in Kenya. By identifying these gaps and challenges, the research will contribute to the development of strategies and recommendations for implementing and enforcing technology into Kenya’s dispute resolution framework. The findings of this study hold potential significance for policymakers and legal practitioners, emphasizing the necessity of updating and adapting the legal framework to support and regulate the use of advanced technologies in dispute resolution.
Full - text undergraduate research project